1984
DOI: 10.1139/v84-307
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity studies of β-carbolines. 2. Crystal and molecular structures of N-ethyl-3-carbamoyl-β-carboline

Abstract: The crystal and molecular structures of N-ethyl-3-carbamoyl-β-carboline, C14H13N3O, a synthetic ligand of the benzodiazepine receptor are reported. The space group is C2/c with a = 16.220(4), b = 7.728(4), c = 19.623(6) Å, β = 104.16(1)°, Z = 8. The carboxyamide side chain assumes an extended conformation and is almost coplanar with the β-carboline skeleton. The observed molecular conformation is compared to the current model for the receptor binding site. Hydrogen bonding and aromatic ring stacking determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…The side chain in each of the unique molecules has approximately the same orientation; the torsion angle, N(2)-C(3)-C(31)=0(34), is 3.2(1)" in one molecule and -5.3(2)" in the other. This orientation places the nitrogen atom of the pyridine fragment of the P-carboline and the carbonyl oxygen atom of the ester side chain in a cis configuration and is opposite to the side chain conformation observed in the carboxyamide derivative of P-carboline (8). In the carboxyamide case, all published examples of that side chain and a similar aromatic N atom were found in the trans configuration.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The side chain in each of the unique molecules has approximately the same orientation; the torsion angle, N(2)-C(3)-C(31)=0(34), is 3.2(1)" in one molecule and -5.3(2)" in the other. This orientation places the nitrogen atom of the pyridine fragment of the P-carboline and the carbonyl oxygen atom of the ester side chain in a cis configuration and is opposite to the side chain conformation observed in the carboxyamide derivative of P-carboline (8). In the carboxyamide case, all published examples of that side chain and a similar aromatic N atom were found in the trans configuration.…”
Section: Discussionmentioning
confidence: 80%
“…The methyl ester has the highest affinity for the receptor of any of the P-carbolines that have been structurally characterized. The X-ray structure determination of CCM is part of an ongoing study of the ligands for this receptor (8). 'This paper has been presented in part: see Abstracts of the 13th International Congress of Crystallography, Acta Crystallogr.…”
mentioning
confidence: 99%
“…, both esters show partial IT stacking which involves the A ring: Such interactions involving the A ring are postulated to be important to receptor binding (10,11). The only other type of IT-stacking observed in P-carboline crystals involved stacking of the side chain over the five-membered ring: this was observed for the low affinity N-ethyl-3-carbamoyl-P-carboline (24).…”
Section: Resultsmentioning
confidence: 99%
“…The trans conformati >n of the ester side chain that was found in the canthin-6-one cr..stal has also been observed in two non-ester benzodiazepin, receptor ligands: the N-ethyl-3-carbamoyl-P-carboline IV (24), which has low benzodiazepine receptor affinity (28), and 3-(methoxycarbony1)amino-pcarboline V (1 2), which produces 50% antagonism of diazepam (111) binding at a concentration of 71 nM (29). Because our examination (24) of the tabulated geometries of pyridyl-carbamoyl fragments showed that trans is the only observed conformation, and because the carbamoyl-P-carboline has low receptor affinity (28), we have proposed (24) that this trans conformation is not the binding conformation. Thus, models for the receptor-ligand interaction have assumed a cis conformation for the ester side chain (9, 13a, b).…”
Section: Discussionmentioning
confidence: 99%
“…The structural features that favor binding of a P-carboline at the BZD receptor have been established (9)(10)(11)(12)(13)(14)(15). They include a planar, unsaturated ring system, a basic pyridyl N atom, an unobstructed indole N-H group, and at least one additional substituent: either (a) a side chain in position 3 that contains a carbonyl oxygen atom or is electron releasing, or (b) a hydrophobic group in position 5 or 6, or (c) an oxygen-containing side chain in position 4.…”
Section: Introductionmentioning
confidence: 99%